The Role of Empathetic Leadership in Human Resource Management: Employee Perspectives in the Era of Remote Work - Rano Kurniawan; Cionita Tezara; Nor F. Yah (Takaza Innovatix Labs Ltd., 2025)
This study explores the impact of empathetic leadership on employee performance, motivation, and well-being in remote work environments at PT Gojek Indonesia. Through semi-structured interviews and observations, the research investigates how empathetic leadership behaviors, such as active listening and emotional support, influence employee engagement and job satisfaction. The findings demonstrate that empathetic leadership enhances employee motivation and reduces stress, contributing to improved performance and organizational commitment. However, challenges in maintaining empathy in digital communication and ensuring consistency in its application across leaders were identified. The study highlights the critical role of empathy in fostering strong leader-member relationships, particularly in virtual settings, and provides practical implications for organizations looking to integrate empathetic leadership into their HRM strategies. The results contribute to the existing literature on leadership by offering empirical evidence on the application of empathy in remote teams and suggest avenues for future research on the long-term effects of empathetic leadership in digital work environments.